Teen beach 2 [videorecording (DVD)] - Phipps, Grace, 1992-; Mitchell, Maia; Lynch, Ross, 1995- (Disney DVD, 2015)
Dive in and rock out with the hottest surf sequel under the sun! Now that summer's over and school has begun, Brady and Mack's relationship seems headed for a wipeout; until Lela, Tanner and the "Wet Side Story" kids show up! Dazzled by the novelty and variety of the modern world, Lela wants to stay, but the real world and the "reel" world just don't mix. Can Mack and Brady find the magic to get the kids home and get their own romance back on track before it's too late?